1999
DOI: 10.1115/1.2798042
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Surface Topography of Micromachined Titanium Substrata on Cell Behavior in Vitro and in Vivo

Abstract: Surface properties, including topography and chemistry, are of prime importance in establishing the response of tissues to biomaterials. Microfabrication techniques have enabled the production of precisely controlled surface topographies that have been used as substrata for cells in culture and on devices implanted in vivo. This article reviews aspects of cell behavior involved in tissue response to implants with an emphasis on the effects of topography. Microfabricated grooved surfaces produce orientation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
259
3
7

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(278 citation statements)
references
References 55 publications
9
259
3
7
Order By: Relevance
“…22 For the smooth materials (SS, TE, and NE), the variation in micro-and nano-topography did not have an adverse influence on cell adhesion, and spreading, nor did it affect cell growth as shown earlier. 9 This corresponds with observations of fibroblast morphology observed on smooth surfaces 23 and previously reported osteoblast reactivity to smooth SS, Ti-6Al-4V, and Thermanox. 24 The standard roughened topography of titanium, to some extent, controlled cell adhesion and shape, though this ultimately presented no difficulty for cells.…”
Section: Discussionmentioning
confidence: 99%
“…22 For the smooth materials (SS, TE, and NE), the variation in micro-and nano-topography did not have an adverse influence on cell adhesion, and spreading, nor did it affect cell growth as shown earlier. 9 This corresponds with observations of fibroblast morphology observed on smooth surfaces 23 and previously reported osteoblast reactivity to smooth SS, Ti-6Al-4V, and Thermanox. 24 The standard roughened topography of titanium, to some extent, controlled cell adhesion and shape, though this ultimately presented no difficulty for cells.…”
Section: Discussionmentioning
confidence: 99%
“…The behaviour of both fibroblasts and osteoblasts was studied. Fibroblasts are the predominant cells found in loose connective tissue and are important in wound repair mechanisms: fibrous encapsulation is caused by the fibroblast type cells adhering to their neighbours rather than the substrate (Brunette and Chehroudi, 1999). Fibroblasts play a role in producing many of the components essential to connective tissue, for example extracellular components such as glycosaminoglycans and, in fibrous tissue, collagen (Rae, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrous encapsulation is known to occur to implants made of steel, usually with the presence of a liquid filled void between the tissue and implant (Woodward and Salthouse, 1986) and is thought to be due to the cells not adhering adequately to the surface (Richards, 1996), resulting in a destabilisation of the implant, an inhibition of tissue regeneration and repair as well as increasing the chances of infection (Albrektsson et al, 1981;Gristina, 1987;Brunette and Chehroudi, 1999). This invariably leads to the rejection and failure of the implant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, cellular response to external stimuli goes far beyond the bare ability of the cell to chemically sense specific ECM ligands and includes a wide range of physical cues that are generated at, or act on, the interface between cells and the surrounding environment. For instance, it has been observed that micrometer-scale roughness may affect cell proliferation and morphology (15,16), because it provides a quasi-biomimetic microenvironment to the cells. However, cell-substrate interactions are typically governed by complex mechanisms occurring at the nanoscale, which are generally referred to as nanobiointeractions (17).…”
mentioning
confidence: 99%